Klimawandelgerechte Stadtentwicklung durch grüne Infrastruktur - Rößler, Rößler (Raumforschung und Raumordnung | Spatial Research and Planning, 2015)
Urban vegetation and green spaces play a crucial role in dealing with the impacts of climate change: urban green spaces regulate the micro-climate in densely built-up and overheated settlement areas, and support the percolation of rain water and the retention of flood events. According to these findings, manifold measures of green space development are discussed, supporting an urban development which is appropriate to the challenges of climate change. Thus, retaining and enhancing the provision of settlement areas with green spaces in terms of green infrastructure is a central element of urban and regional climate adaptation strategies. In this paper the question is raised, how green infrastructure and its different potentials to adapt to climate change can be considered in the urban fabric and measures to enhance the green infrastructure can be implemented. As a part of the “Integrated Regional Climate Adaptation Programme for the Region of Dresden” a number of measures for the development and planning of green infrastructure have been developed. Based on these experiences, basic planning approaches to implement and realise green infrastructure, addressing climate adaptation both on city and site scale, are presented.